Comparative perspectives on East and West European defence industries - Brian Kenny (Journal for East European Management Studies, 2001)
Coupled with the continuing threat of reduced defence expenditures and increasing competition, European defence companies have reacted with a number of strategic manoeuvres involving mergers, acquisitions and other forms of alliance. Moves towards a single European defence industry have been a focus for discussion among major EU member countries for some time and the integration of defence aerospace organisations seems well placed to succeed with the advent of EADS. Defence industry firms and managers from the former Visegrad countries appear to share similar experiences and cultural characteristics with their western counterparts. With their recent incorporation of the Czech Republic and Poland into NATO, their integration into a wider European defence industry could be a viable option. However, there are particular economic, political, cultural and managerial problems to be faced and surmounted before wider and fuller integration can be achieved. – – Europäische Unternehmen der Rüstungstechnik reagieren auf die Gefahren weiterer Budgetkürzungen der Verteidigungshaushalte und zunehmenden Konkurrenzdruckes mit strategischen Umstrukturierungen, vor allem Fusionen, Übernahmen und anderen Formen von Unternehmenszusammenschlüssen. Die größeren EU-Mitgliedsstaaten diskutieren Wege zu einer vereinten europäischen Rüstungsindustrie, und die Integration von Unternehmen der Rüstungs-, Luft- und Raumfahrttechnik geht gut voran. Manager von Unternehmen der ehemaligen Visegrad-Staaten haben vieles mit ihren westlichen Kollegen in punkto Persönlichkeit und Erfahrungen gemein. Eine NATO-Erweiterung in dieser Richtung bietet dann auch die Möglichkeit einer ebenso ausgedehnten vereinten europäischen Rüstungsindustrie.
Keywords: 650